Building a Bridge to the New Normal in the Province of South Kalimantan, Indonesia and the State of California, America - Riinawati Riinawati; Rusnadi Rusnadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The existence of the COVID-19 pandemic definitely has an influence on many aspects of life, including schooling. Various efforts continue to be strengthened in the implementation of this educational process so that educational goals may still be met throughout the epidemic. The government continues to issue policies in responding to changing situations. Educational institutions must be able to provide innovations that are consistent with pandemic policies. In order to establish bridges to the new normal, this research identified and assess policies, methods, and models for implementing education in the post-COVID-19 era. This study is a case study in the province of South Kalimantan, Indonesian and the State of California in the United States. The literature review or study research approach was employed.Â The findings reveal that, despite a policy of allowing for limited face-to-face schooling, health protocols in Kalimantan were still strictly enforced. Meanwhile, in California, learning is performed entirely face-to-face, reducing social alienation, despite the fact that wearing a mask is still required. Blended learning was employed as an effective and efficient way to accomplish learning objectives.Adanya pandemi COVID-19 tentunya memberikan pengaruh pada banyak aspek kehidupan, termasuk sekolah. Berbagai upaya terus dikuatkan dalam pelaksanaan proses pendidikan ini agar tujuan pendidikan tetap dapat terpenuhi sepanjang masa wabah ini. Pemerintah terus mengeluarkan kebijakan dalam menanggapi situasi yang berubah. Lembaga pendidikan harus mampu memberikan inovasi yang sejalan dengan kebijakan pandemi. Dalam rangka menjembatani new normal, penelitian ini mengidentifikasi dan mengkaji kebijakan, metode, dan model penyelenggaraan pendidikan di era pasca-COVID-19. Penelitian ini merupakan studi kasus di provinsi Kalimantan Selatan, Indonesia dan Negara Bagian California di Amerika Serikat. Tinjauan literatur atau pendekatan penelitian studi digunakan. Temuan mengungkapkan bahwa, meskipun ada kebijakan yang mengizinkan sekolah tatap muka terbatas, protokol kesehatan di Kalimantan masih ditegakkan dengan ketat. Sementara itu, di California, pembelajaran dilakukan sepenuhnya dengan tatap muka, mengurangi keterasingan sosial, meskipun penggunaan masker tetap diperlukan. Blended learning digunakan sebagai cara yang efektif dan efisien untuk mencapai tujuan pembelajaran.